Arthroscopic Treatment of Perilunate Dislocations and Fracture Dislocations - Kim, Jong Pil; Lee, Jae Sung; Park, Min Jong (Journal of Wrist Surgery, 2015)
Background The key to a successful result in the treatment of perilunate dislocations (PLDs) and fracture-dislocations (PLFDs) is the restoration of normal alignment of the carpal bones, followed by stable maintenance until healing. This article aimed to assess whether arthroscopic techniques are a reliable surgical option for the treatment of this challenging injury.Materials and Methods Twenty patients with an acute PLD or PLFD were treated by an arthroscopic technique. They were retrospectively reviewed at an average follow-up of 31.2 months (range 18–61 months). Functional outcomes were assessed with the Modified Mayo Wrist Score (MMWS), Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, and Patient-Rated Wrist Evaluation (PRWE) score as well as radiographic evaluations.Description of Technique Arthroscopic reduction and percutaneous fixation was performed to the scapholunate and lunotriquetral intervals using Kirschner wires (K-wires) as joysticks as well as to the scaphoid using a cannulated headless screw for transscaphoid-type injuries. The K-wires were removed at 10 weeks postoperation.Results Overall functional outcomes according to the MMWS were rated as excellent in three patients, good in eight, fair in seven, and poor in two. The mean DASH score was 18, and the mean PRWE score was 30. On the basis of radiographic parameters, reduction obtained at the operation was maintained within normal ranges in 15 patients. No patient had developed arthritis by the last follow-up.Conclusions The medium-term results show that arthroscopic treatment can provide proper restoration and stable fixation of carpal alignment and results in satisfactory functional and radiologic outcomes for acute perilunate injuries.Level of Evidence Level IV.
Keywords: arthroscopy; perilunate; dislocation; fracture-dislocation; percutaneous